Intervention in Crisis: Understanding the Role of Mental Illness in Bystander Decision-Making Using Audio Vignettes - Harris, Michelle N. (Criminal justice and behavior, 2025)
Research highlights that people with mental illness are significantly more likely to experience victimization events compared with the general population. Generally, studies have noted the importance of guardianship in preventing victimization among this population; however, prior investigations have neglected to examine the role of bystanders’ willingness to intervene in risky scenarios involving a person exhibiting mental illness. To address this gap, this study utilizes data collected from a factorial survey design and audio vignettes to explore how situational and individual-level characteristics influence indirect bystander intervention in scenarios involving a hypothetical victim displaying signs of mental illness. Findings show that participants were significantly less likely to intervene in situations involving a victim exhibiting signs of mental illness. Indirect bystander intervention was also influenced by victim/offenders’ sex, location of the event, severity of aggression, and participants’ personal ties to mental illness, particularly through romantic relationships. Implications for intervention are discussed.